Les oiseaux forestiers montrent-ils la même sensibilité à l’exploitation forestière aux échelles du peuplement et du paysage ? - Marc-André Villard; Jean-Sébastien Guénette (VertigO)
In forest ecosystems, birds represent a species-rich taxon which is relatively easy to survey over large spatial scales. Hence, forest birds (mainly passerines and woodpeckers) have been the focus of numerous studies aiming to assess biological response to forest harvesting. This study aims to determine the comparability of forest bird response to forestry at local (here, 80-m radius circle) and landscape (1-km radius) scales. In other words, can we extrapolate responses to harvesting from one spatial scale to the other? We examined bird response to harvesting using logistic regression models on the presence-absence of 42 species at 390 point count stations located in the Black Brook District, a managed forest landscape of northwestern New Brunswick. Absences were validated using a total of 45 min of observation distributed among three visits during the breeding season. Twenty-five of the 42 species responded positively or negatively to forest harvesting at the local scale, and 14 at the landscape scale. Only 6 of the 14 species responded in the same fashion at both scales. These results indicate that we should integrate the particular response of species both at local and landscape scales when planning sustainable forest management.